Perilaku Ramah Lingkungan Masyarakat Pesisir dalam Perspektif Operant Conditioning Theory: Studi Kasus di Bangsal, Desa Pemenang Barat, KLU - Bella Hafiza; Ibrahim; Syafril (Mataram University, 2026)
This study aims to analyze the pro-environmental behavior of coastal communities in Bangsal, West Pemenang Village, North Lombok, through the perspective of Operant Conditioning Theory. A descriptive qualitative approach was employed to understand community action patterns in maintaining coastal environmental cleanliness. Data were collected through observation, in-depth interviews, and documentation, involving informants such as fishermen, boat crews, traders, cooperative managers, boat service owners, tourists, sanitation workers, youth leaders, and village officials. The findings indicate that pro-environmental behavior has emerged, particularly among fishermen, boat crews, and traders; however, these actions have not yet been institutionalized due to the lack of formal regulations, weak sanction mechanisms, and the absence of structured positive reinforcement. Tourists are identified as the primary contributors to waste generation, while natural conditions such as adverse weather exacerbate the situation. Given the inadequacy of current waste management, the village government is initiating efforts to establish a Village Regulation and a Community Self-Help Group (KSM) to strengthen waste governance. The operant conditioning analysis shows that ecological behavior in Bangsal is still largely driven by intrinsic and economic reinforcement, with no clear punishment mechanisms in place. This study highlights the need for systematic behavior-based reinforcement interventions to foster sustainable environmental habits. The findings contribute theoretically to the application of B. F. Skinner’s theory in coastal contexts and provide practical implications for community-based waste management policy development.